Reappraisal of Eiconaxius farreae Ortmann, 1891 and Eiconaxius mortenseni Sakai, 1992 (Decapoda: Axiidea: Axiidae), with description of a new species from Japan - Komai, Tomoyuki (Zootaxa, 2024)
The sponge associated axiid shrimp Eiconaxius farreae Ortmann, 1891 was originally described based on specimens from Sagami Bay, central Japan. Morphological examination of many specimens of Eiconaxius collected from Sagami Bay and nearby areas, and genetic data from the mitochondrial COI and 16S rRNA genes have revealed that three species are represented. This finding led to a reappraisal of the identity of E. farreae and E. mortenseni Sakai, 1992, also originally described from Sagami Bay. It has been clarified that two species (E. farreae and an undescribed species) were mixed in the syntype material of E. farreae, and consequently, a lectotype of E. farreae is designated in the interest of nomenclatural stability. Here, E. farreae and E. mortenseni are redescribed, and the third species is described as new, E. reconditus. The new species is morphologically very similar to E. mortenseni. Differentiating characters among closely allied species are reassessed. Previous records of E. farreae are reviewed in light of the present findings.